Case report of a Japanese patient with chronic renal failure who developed SARS‐CoV‐2 in a hospital cluster during treatment for acute respiratory failure: An autopsy report - Yoshifumi Amari; Satoshi Morimoto; Takashi Teranishi; Mai Ohata; Atsushi Takeshita; Hiroshi Hirano; Hitoshi Kobayashi (Clinical Case Reports, 2022)
Abstract This article reports a clinical and histopathological perspective which noted not only COVID‐19 pneumonia but also exacerbation of chronic renal failure potentially caused by thrombus in the kidney, possibly COVID‐19‐related lesions. The accumulation of autopsy cases will elucidate the pathogenesis of COVID‐19 and aid in the development of effective therapeutics.